Synthesis of 1-indolyl-3,5,8-substituted γ-carbolines: one-pot solvent-free protocol and biological evaluation - Dudhe, Premansh; Krishnan, Mena Asha; Yadav, Kratika; Roy, Diptendu; Venkatasubbaiah, Krishnan; Pathak, Biswarup; Chelvam, Venkatesh (Beilstein Journal of Organic Chemistry, 2021)
1,5-Disubstituted indole-2-carboxaldehyde derivatives 1a–h and glycine alkyl esters 2a–c are shown to undergo a novel cascade imination-heterocylization in the presence of the organic base DIPEA to provide 1-indolyl-3,5,8-substituted γ-carbolines 3aa–ea in good yields. The γ-carbolines are fluorescent and exhibit anticancer activities against cervical, lung, breast, skin, and kidney cancer cells.
Keywords: γ-carboline; cascade reaction; cell uptake; cytotoxicity; fluorescence

(untitled) - Reniers, J.; Robert, S.; Frederick, R.; Masereel, B.; Vincent, S.; Wouters, J. (Bioorg. Med. Chem., 2011)

(untitled) - Alekseyev, R. S.; Kurkin, A. V.; Yurovskaya, M. A. (Khim. Geterotsikl. Soedin., 2009)

(untitled) - Pontecorvo, M. J.; Devoussr, M. D.; Navitsky, M.; Lu, M.; Salloway, S.; Schaerf, F. W.; Jennings, D.; Arora, A. K.; McGeehan, A.; Lim, N. C.; Xiong, H.; Joshi, A. D.; et al. (Brain, 2017)

Int. Pat. Appl. - Snyder, J. K.; Wei, G. W.; Strosberg, A. D.; Kota, S.; Takahashi, V. (Small Molecule Inhibitors of Hepatitis C Virus, 2010)

(untitled) - Guerquin-Kern, J.-L.; Coppey, M.; Carrez, D.; Brunet, A.-C.; Nguyen, C. H.; Rivalle, C.; Slodzian, G.; Croisy, A. (Microsc. Res. Tech., 1997)

(untitled) - Ran, X.; Zhao, Y.; Liu, L.; Bai, L.; Yang, C.-Y.; Zhou, B.; Meagher, J. L.; Chinnaswamy, K.; Stuckey, J. A.; Wang, S. (J. Med. Chem., 2015)

(untitled) - Ibrahim, S. R. M.; Mohamed, G. A.; Zayed, M. F.; Sayed, H. M. (Drug Res. (Stuttgart, Ger.), 2015)

(untitled) - Naik, P. N.; Khan, A.; Kusurkar, R. S. (Tetrahedron, 2013)

(untitled) - Jia, T.; Wang, J.; Guo, P.; Yu, J. (Org. Biomol. Chem., 2015)

(untitled) - Otto, R.; Penzis, R.; Gaube, F.; Winckler, T.; Appenroth, D.; Fleck, C.; Tränkle, C.; Lehmann, J.; Enzensperger, C. (Eur. J. Med. Chem., 2014)

(untitled) - Shuvalov, V. Y.; Shestakov, A. N.; Kulakova, L. A.; Kuratova, A. K.; Vorontsova, M. A.; Sagitullina, G. P. (Khim. Geterotsikl. Soedin., 2019)

(untitled) - Alekseev, R. S.; Kurkin, A. V.; Yurovskaya, M. A. (Khim. Geterotsikl. Soedin., 2012)

(untitled) - Harbert, C. A.; Plattner, J. J.; Welch, W. M.; Weissman, A.; Koe, B. K. (J. Med. Chem., 1980)

(untitled) - Butler, K. V.; Kalin, J.; Brochier, C.; Vistoli, G.; Langley, B.; Kozikowski, A. P. (J. Am. Chem. Soc., 2010)

(untitled) - Zhang, H.; Larock, R. C. (Tetrahedron Lett., 2002)

(untitled) - Subba Reddy, B. V.; Swain, M.; Reddy, S. M.; Yadav, J. S.; Sridhar, B. (J. Org. Chem., 2012)

(untitled) - Nissen, F.; Richard, V.; Alayrac, C.; Witulski, B. (Chem. Commun., 2011)

(untitled) - Wang, T.-T.; Zhang, D.; Liao, W.-W. (Chem. Commun., 2018)

(untitled) - Gutiérrez, S.; Sucunza, D.; Vaquero, J. J. (J. Org. Chem., 2018)

(untitled) - Chepyshev, S. V.; Lujan-Montelongo, J. A.; Chao, A.; Fleming, F. F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Hao, W.-J.; Wang, S.-Y.; Ji, S.-J. (ACS Catal., 2013)

(untitled) - Lee, Y.; Klausen, R. S.; Jacobsen, E. N. (Org. Lett., 2011)

(untitled) - Touré, B. B.; Hall, D. G. (Chem. Rev., 2009)

(untitled) - Held, F. E.; Guryev, A. A.; Fröhlich, T.; Hampel, F.; Kahnt, A.; Hutterer, C.; Steingruber, M.; Bahsi, H.; von Bojničić-Kninski, C.; Mattes, D. S.; Foertsch, T. C.; Nesterov-Mueller, A.; et al. (Nat. Commun., 2017)

(untitled) - Tietze, L. F.; Rackelmann, N. (Pure Appl. Chem., 2004)

(untitled) - Tietze, L. F.; Modi, A. (Med. Res. Rev., 2000)

(untitled) - Nicolaou, K. C.; Edmonds, D. J.; Bulger, P. G. (Angew. Chem., Int. Ed., 2006)

(untitled) - Dai, J.; Dan, W.; Zhang, Y.; Wang, J. (Eur. J. Med. Chem., 2018)

(untitled) - Martin, S. F. (Pure Appl. Chem., 2009)

(untitled) - López-Pérez, A.; Adrio, J.; Carretero, J. C. (Angew. Chem., Int. Ed., 2009)

(untitled) - Dudhe, P.; Venkatasubbaiah, K.; Pathak, B.; Chelvam, V. (Org. Biomol. Chem., 2020)

(untitled) - Das, T.; Kayet, A.; Mishra, R.; Singh, V. K. (Chem. Commun., 2016)

(untitled) - Zhao, G.-J.; Liu, J.-Y.; Zhou, L.-C.; Han, K.-L. (J. Phys. Chem. B, 2007)